ASSA14-03-32 Over restrictive salt diet promotes dyslipidemia via up-regulating PCSK9 in ApoE-deficient mice. (1st December 2014) - Zhu, N; Han, Y; Zhang, X; Zhao, X; Zhang, Y; Yan, C
Abstract : Background: Hyperlipidemia is one of most important detrimental risk factors in leading cardiovascular disease, but the underlying mechanism remains in heated discussion. Recently, studies reporting a low salt intake could lead to dyslipidemia attracted extensive attention and query. The authenticity and possible aetiology need to be discussed in-depth. Proprotein convertase subtilisin/kexin 9(PCSK9), a vital regulator of low-density lipoprotein (LDL)-cholesterol levels, is closely related to hyperlipidemia. Here, we investigated whether restrictive salt could lead to dyslipidemia and role of PCSK9 in regulating this process in ApoE -/- mice. Method: Male mice aged 10-weeks between 20 to 25 g were allocated to receive an isocaloric diet with low-salt content (0.03%), low-salt diet (0.03%) combined with PCSK9 siRNA tail injection, normal salt content (0.3%) or a high-salt content (3%) containing 20% fat. After 8 weeks of feeding, the basic metabolic index, including weight, blood pressure, urine sodiumand urine potassiumwere evaluated. After anaesthetised by chloral hydrate, blood was collected by exsanguination via carotid artery. Total cholesterol, triglycerides and LDL-c were measured in fasting plasma samples using an auto-analyzer. The expression of PCSK9 in liver was measured by immunohistochemistry and Western blot. Results: Eight-weeks of a low-salt diet resulted in increased cholesterol, LDL-c and triglyceride in ApoE -/- when compared with mice receiving normal salt, while a high-salt diet attenuated the dyslipidemia. Then the expression of PCSK9 was detected by immunohistochemistry and western blot in liver, the result showed that a low salt diet increased PCSK9 in liver, by contrast, a high-salt diet decreased PCSK9 level compared to normal salt diet group. A low salt diet combined PCSK9 siRNA could suppress the lipid increasing. Conclusions: Over restrictive salt could cause dyslipidemia, and one of the possible mechanisms is up-regulating the expression of PCSK9 in ApoE -/- mice. This finding provides mechanistic insights on low salt diet associated dyslipidemia.